Faktor-Faktor Yang Berhubungan Dengan Tingkat Kepatuhan Minum Obat Antihipertensi Pasien Di Puskesmas Kecamatan Wilayah Jakarta Utara - Wiwid Cahyati, Elisabeth Carisa; Ni Luh Widani; Sada Rasmada (PT. Pubsains Nur Cendekia, 2024)
Hypertension is a non-communicable disease that can be controlled through lifestyle modifications or antihypertensive therapy. Antihypertensive therapy is a long-term therapy which might even last a lifetime, so it needs a high compliance to taking antihypertensive therapy to achieve blood presure target. This study aims to identify the factors associated with the level of adherence in taking antihypertensive medication by using references from 2012-2023. Quantitative research method with cross sectional research design and correlational descriptive approach was conducted to 120 hypertension respondents at District Health Center North Jakarta in June-July 2023. The instruments used in this research were attitude, knowledge and MMAS-8 questionnaires. Data analysis used Kendal's tau-b, Kendal's tau-c and chi square statistical tests. The univariat results of the study showed that there were 2 respondents with high compliance, 19 respondents with moderate compliance, and 99 respondents with low compliance. The majority of respondents are (35%) adults, (55%) male, (69,25%) are employee, (50%) are secondary school students, (49,2%) are good knowledge, (45,8%) are good attitude, and (56,7%) with drugs combination. Bivariate results showed there was a relationship between the level of adherence to taking antihypertensive medication and age (p-value = 0.002), education (p-value = 0.000), drug combination (p-value = 0.003), knowledge and attitude (p-value = 0.002. In summary, the compliance of respondents is low, and there was a relationship between age, education, combination of drugs, knowledge, attitudes and the level of adherence to taking antihypertensive medication. While gender, occupation and duration of therapy were not related to the level of adherence to taking antihypertensive medication.